GANGGUAN FUNGSI MOTOR PADA PENDERITA HIPERTENSI KAJIAN BIOMOLEKULER - Darwin Amir* (Neurona Majalah Kedokteran Neuro Sains, 2010)
INTRODUCTION HYPERTENSION AS A RISK FACTOR FOR CEREBROVASCULAR DISEASE HAS LONG BEEN RECOGNIZED INCIDENCE RATES OF THIS DEGENERATIVE DISEASE TENDED TO INCREASE AND ACCORDING TO THE WHO HYPERTENSION IS A PANDEMIC HEALTH PROBLEMS WHICH IMPACTED ON MORBIDITY AND MORTALITY AT THE STAGE OF PREPATHOGENESIS OF CVDS COMPLICATIONS HYPERTENSION HAS AFFECTED VARIOUS FUNCTIONS SUCH AS COGNITIVE FUNCTION EXECUTIVE FUNCTION AND MOTOR CONTROL AND SPEED